not a tourist - McGregor, Carol (Tamworth Regional Gallery, 2017)
Research Background: McGregor’s not a tourist (2017) emerged from the artist considering her heritage, particularly her paternal Aboriginal great-grandmother, Annie, and maternal non-Indigenous grandmother, Clara. Additionally, a photograph of a possum-skin bag (c.1870, from the historical First Nations digital image collection McGregor accessed as a Museum Victoria Scholar in 2015) similar to those McGregor’s great-grandmother may have used. Inspired by the image, and having previously worked with possum skins, McGregor gained permission to remake the possum-skin bag. Using traditional Aboriginal methods McGregor spun possum fur and natural wool, weaving memories into three dilly bags. Aspects of identity and symbols of McGregor’s family narrative were knitted from a ball of yarn made from strips of ochred possum skin. The dilly bags anchor possibilities of mutual respect and understanding. Using tea towels bearing kitsch representations of Australian Aboriginal people and artefacts, the printed images are reversed to signify “turning my back on the systematic corruption of our Indigenous culture” (McGregor, 2017). Research Contribution: In 2015 McGregor gained access to historical First Nations digital image collection as a Museum Victoria Scholar. McGregor reveals the traditional use of possum fur in string making and dilly bags through the utilisation colonial archives to stimulate the making of traditional and contemporary cultural items. Research Significance: not a tourist (2017) was acquired by the Tamworth Regional Gallery collection. It was first exhibited in Open House: 3rd Tamworth Textile Triennial (2017), Tamworth Regional Gallery. Curated by Glenn Barkley and toured nationally 2018-2020. No Full Text